Evaluasi kinerja dan efisiensi pompa sentrifugal pada sistem pengolahan minyak mentah : studi kasus PT. X - Patria, Mochamad Febrian Adhi; Ramadhan Bhakti Saputra, Surya (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2026)
Centrifugal pump P100/5 is used to transfer crude oil from the feed tank to the oil processing system at of Refinery PT.X. Evaluating performance and efficiency is essential to ensure the reliability and effectiveness of the processing operation. This study aims to evaluate the performance efficiency of centrifugal pump P.100/5 under actual operating conditions. The research employs a quantitative approach by calculating key performance parameters, including flow rate, head, and pump power. The results indicate that centrifugal pump P.100/5 (Ebara Corporation, 2007), with a design capacity of 25 m³/h and a motor power of 15 kW, has an efficiency performance of 40.94%. This value is still considered acceptable; however, it is not optimal. The primary factor affecting the low efficiency is the oversizing condition, where the pump capacity exceeds the actual system demand. As a result, flow regulation is carried out using a throttling method, which increases head loss and reduces pump efficiency. Several improvement strategies can be applied, including adjusting pump specifications to operate closer to the Best Efficiency Point (BEP), implementing routine maintenance, preventing cavitation, and optimizing system operation. Among these alternatives, the use of a Variable Frequency Drive (VFD) is identified as the most effective solution, as it allows the pump rotational speed to be adjusted according to actual demand, thereby improving energy efficiency and minimizing system losses.